THE IMPLEMENTATION OF TEAM GAMES TOURNAMENT (TGT) MODELS TO IMPROVE SELF-CONFIDENCE AND SPEAKING SKILLS (Case study at English subject of eighth Grade Student of SMPN 01 Lebong) - Intan Prilia; Bambang Sahono (DIADIK, 2019)
This research aims to describe the improvement in self-confidence and speaking skills of students in English subjects in the eighth grade of SMP N 01 Lebong by applying the TGT learning model. The research conducted was classroom action research combined with quasi-experiment. The subjects of this study were grade VIII. The instruments used are observation and test sheets. The data analysis technique uses the average formula for the percentage of classical learning completeness and t-test, while the observation data is analyzed by the average score, highest score, lowest score, difference in score, and range of values for each criterion. The results showed that the implementation of the team games tournament (TGT) type learning model improve students' self- confidence and speaking skills